CEREBROTENDINOUS XANTHOMATOSIS - Awan, Zahid A; Rehman, Anees -ur-; Khan, Alaf (Journal of Ayub Medical College Abbottabad, 1996)
Hypercholesterolemia is a well-known risk factor for coronary heart disease, however we report a very rare disorder of lipid metabolism which is associated with coronary heart disease despite the fact that all the basic risk markers of dislipdemia like serum cholesterol, HDL, LDL and triglycerides are normal.